Thermo‐erosional valleys in Siberian ice‐rich permafrost - Morgenstern, Anne; Overduin, Pier Paul; Günther, Frank; Stettner, Samuel; Ramage, Justine; Schirrmeister, Lutz; Grigoriev, Mikhail N.; Grosse, Guido (FID GEO, 2020)
Thermal erosion is a major mechanism of permafrost degradation, resulting in characteristic landforms. We inventory thermo‐erosional valleys in ice‐rich coastal lowlands adjacent to the Siberian Laptev Sea based on remote sensing, Geographic Information System (GIS), and field investigations for a first regional assessment of their spatial distribution and characteristics. Three study areas with similar geological (Yedoma Ice Complex) but diverse geomorphological conditions vary in valley areal extent, incision depth, and branching geometry. The most extensive valley networks are incised deeply (up to 35 m) into the broad inclined lowland around Mamontov Klyk. The flat, low‐lying plain forming the Buor Khaya Peninsula is more degraded by thermokarst and characterized by long valleys of lower depth with short tributaries. Small, isolated Yedoma Ice Complex remnants in the Lena River Delta predominantly exhibit shorter but deep valleys. Based on these hydrographical network and topography assessments, we discuss geomorphological and hydrological connections to erosion processes. Relative catchment size along with regional slope interact with other Holocene relief‐forming processes such as thermokarst and neotectonics. Our findings suggest that thermo‐erosional valleys are prominent, hitherto overlooked permafrost degradation landforms that add to impacts on biogeochemical cycling, sediment transport, and hydrology in the degrading Siberian Yedoma Ice Complex. : Christiane Nüsslein‐Volhard Foundation : European Research Council http://dx.doi.org/10.13039/501100000781 : German Academic Exchange Service DAAD P.R.I.M.E. : Helmholtz‐Gemeinschaft http://dx.doi.org/10.13039/501100001656 : Polar Geospatial Center, NSF‐OPP awards : RapidEye Science Archive (RESA) : Russian Foundation for Basic Research http://dx.doi.org/10.13039/501100002261 : Studienstiftung des Deutschen Volkes http://dx.doi.org/10.13039/501100004350 : Universität Potsdam http://dx.doi.org/10.13039/501100004238 : BMBF KoPf